2001
DOI: 10.1093/nar/29.19.3982
|View full text |Cite
|
Sign up to set email alerts
|

Class-1 translation termination factors: invariant GGQ minidomain is essential for release activity and ribosome binding but not for stop codon recognition

Abstract: Previously, we have shown that all class-1 polypeptide release factors (RFs) share a common glycine-glycine-glutamine (GGQ) motif, which is critical for RF activity. Here, we subjected to site-directed mutagenesis two invariant amino acids, Gln185 and Arg189, situated in the GGQ minidomain of human eRF1, followed by determination of RF activity and the ribosome binding capacity for mutant eRF1. We show that replacement of Gln185 with polar amino acid residues causes partial inactivation of RF activity; Gln185I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(129 citation statements)
references
References 29 publications
3
126
0
Order By: Relevance
“…We have substituted amino acids in the NIKS motif and around it, followed by measuring the ability of the mutant eRF1 to promote fMet-tRNA hydrolysis ("catalytic" or RF activity) and the ribosome binding capacity+ In the latter case, eRF3 GTPase activity, which is entirely eRF1 dependent and ribosome dependent (Frolova et al+, 1996), served as a measure of the eRF1 binding to the ribosome Seit-Nebi et al+, 2001)+ It seems advantageous that this assay is performed in the absence of fMet-tRNA, mRNA, and stop codons (see Materials and Methods)+ Therefore, the GTPase activity measured in this work reflects the affinity of eRF1 toward the ribosome itself but not to mRNA and/or fMet-tRNA+ From comparison of RF and GTPase activities, one may attempt to distinguish between amino acids involved in RBS or in TCRS or in both+ To identify the TCRS, it is compulsory to follow the response of mutant eRF1 to all three stop codons+ If the response varies toward different stop codons, it implies that the given amino acid residue of eRF1 could potentially be involved in stop codon recognition+…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have substituted amino acids in the NIKS motif and around it, followed by measuring the ability of the mutant eRF1 to promote fMet-tRNA hydrolysis ("catalytic" or RF activity) and the ribosome binding capacity+ In the latter case, eRF3 GTPase activity, which is entirely eRF1 dependent and ribosome dependent (Frolova et al+, 1996), served as a measure of the eRF1 binding to the ribosome Seit-Nebi et al+, 2001)+ It seems advantageous that this assay is performed in the absence of fMet-tRNA, mRNA, and stop codons (see Materials and Methods)+ Therefore, the GTPase activity measured in this work reflects the affinity of eRF1 toward the ribosome itself but not to mRNA and/or fMet-tRNA+ From comparison of RF and GTPase activities, one may attempt to distinguish between amino acids involved in RBS or in TCRS or in both+ To identify the TCRS, it is compulsory to follow the response of mutant eRF1 to all three stop codons+ If the response varies toward different stop codons, it implies that the given amino acid residue of eRF1 could potentially be involved in stop codon recognition+…”
Section: Resultsmentioning
confidence: 99%
“…The second functionally essential site of class-1 RFs recognizing stop codons should be remote from the "catalytic" site and positioned near the 30S/40S and 50S/60S interface in the ribosomal particle+ Mutagenesis of yeast eRF1 followed by in vivo genetic assay points to the N domain (Song et al+, 2000) as a region of eRF1 where the termination codon recognition site (TCRS) is located (Bertram et al+, 2000)+ The N-terminal domain (domain 1) of human eRF1 contains a conserved NIKS motif (positions 61-64 for human eRF1), common for Eukarya and Archaea Song et al+, 2000;Fig+ 1A)+ The third functional site(s), a ribosome binding site(s) (RBS), should be located at the N and M domains, as human eRF1 lacking the C domain binds to the ribosome and is functionally active in vitro + This suggestion is consistent with the fact that these domains are topologically distinct (Song et al+, 2000) and have to be fixed within the ribosome separately to ensure fidelity of two main joint functions of class-1 RFs, recognition of stop codons, and promotion of peptidyl-tRNA ester bond hydrolysis+ Mutations in the M domain reduce the ribosome binding ability of human eRF1 (Seit-Nebi et al+, 2001)+ The class-2 termination factors, eRF3/RF3, are known to be GTPases (Frolova et al+, 1996;Freistroffer et al+, 1997;Pel et al+, 1998)+ The human eRF1 and eRF3 interact through their C termini (Merkulova et al+, 1999) and this mutual binding is critical for manifestation of eRF3 GTPase activity within the ribosome (Frolova et al+, 1996+ This property can be used to detect the binding of eRF1 to eRF3 and to the ribosome+ Because the N and M domains of the eRF1 molecule are required to activate eRF3 GTPase, although they are not involved in eRF3 binding, it means that the eRF1 binding to the ribosome is a prerequisite for its activating function toward eRF3 GTPase+ Therefore, the capacity of mutant eRF1 to bind to the ribosome may be followed by measuring the ability of mutant eRF1 to activate eRF3 GTPase if mutations are located within N and/or M domains of eRF1 (Seit-Nebi et al+, 2001)+ Here, we approach the problem of structure and location of eRF1 functional sites, TCRS and RBS, by examining the properties of the human eRF1 NIKS tetrapeptide and adjacent amino acids by site-directed mutagenesis+ This region seems to be a good candidate for being involved either in interaction with the ribosome and/or with stop codons due to their essential and specific features+ The NIKS motif is composed of two invariant amino acids, Ile62 and Lys63 (numbering corresponds to human eRF1; Fig+ 1A), and two conserved but not invariant residues, Asn61 and Ser64 Song et al+, 2000)+ The NIKS motif occupies a well-defined region at the extremity of the N domain (Song et al+, 2000;Fig+ 1B) and has been suggested to be involved both in the ribosome binding and stop codon recognition (Knight & Landweber, 2000)+…”
Section: Introductionmentioning
confidence: 99%
“…C12orf65 is not directly participating in the translation machinery but is an auxiliary factor and was hypothesized to be involved in recycling of abortive peptidyl-tRNA in the mitoribosome. 6 The entire group of the organellar release-factor family is characterized by the presence of a conserved peptidyl-hydrolase domain containing the universally conserved Gly-Gly-Gln (GGQ) motif, 7 which interacts with the large ribosomal subunit to release the polypeptide chain from the P-site bound peptidyl-tRNA. This GGQ-containing domain stretching from amino acid 57 to 121 in the human 166-residue full-length protein 8 is not affected by the mutations that lead to a relatively mild phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The conserved GGQ amino-acid motif that is essential to peptidyl-tRNA hydrolysis is located at the distal end of domain 3 [59,60], whereas the SPF loop that is essential to stop codon recognition is located in domains 2 and 4, which form a compact super-domain [54]. Overall, NMA reveals that domain 3 exhibits the highest conformational flexibility relative to the remainder of the molecule, as measured by root-mean-square fluctuations (RMSFs) (Figure 2).…”
Section: Ribosome-bound Termination Factor Rf2mentioning
confidence: 99%